Synthesis, structural study and thermal behaviour of a new compound: trirubidium bis(hydrogen sulphate) dihydrogen arsenate Rb3(HSO4)2.5(H2AsO4)0.5. (1st February 2017) - Jaouadi, K.; Zouari, N.; Mhiri, T.
ABSTRACT: Mixed crystals Rb3 (HSO4 )2.5 (H2 AsO4 )0.5 have been prepared by slow evaporation from aqueous solution at room temperature. The crystals were characterized by X-ray single analysis, which revealed that Rb3 (HSO4 )2.5 (H2 AsO4 )0.5 crystallizes in the space group P with lattice parameters: a = 7.471(3) Å; b = 7.636(1) Å; c = 12.193(2) Å; α = 71.91(1)°; β = 73.04(6)° and γ = 88.77(2)°. In this structure, the ordered S(1)O4 and the disordered S(3)/AsO4 tetrahedra are connected by O–H..O hydrogen bonds, to a zigzag chains running in the b -direction. These chains are, in turn, bonded to one another by disordered hydrogen bridges O–H..H–O, to give a planar structure, with hydrogen-bonded sheets, laying parallel to (1 0 0). Each disordered tetrahedron is linked to a tetrahedron neighbouring S(2)O4 by ordered hydrogen bonds. Broader peaks in IR spectrum of the title material support the assumption of disordered structure. Thermal analysis of the superprotonic transition in Rb3 (HSO4 )2.5 (H2 AsO4 )0.5 showed that the transformation to the high-temperature phase occurs by one-step process at 404 K. Thermal decomposition of this compound takes place at much higher temperatures, with an onset of approximately 473 K.